Inflammatory bowel diseases and Takayasu's arteritis: coincidence or association?. (23rd February 2016) - Kilic, Levent; Kalyoncu, Umut; Karadag, Omer; Akdogan, Ali; Dogan, Ismail; Bilgen, Sule Apras; Kiraz, Sedat; Ertenli, Ihsan
Abstract: Background: Takayasu's arteritis (TA) and inflammatory bowel disease (IBD) are rare diseases but there are case reports presenting their co‐existence in the literature. The aim of this study was to investigate the relation between IBD and TA. Methods: We studied 52 consecutive TA patients (90.3% female); medical records of the patients were analyzed retrospectively and serum samples were taken during the control visits for anti‐neutrophil cytoplasmic antibody (ANCA) and anti‐saccharomyces antibody (ASCA) tests. Results: Overall three (5.8%) of 52 patients had both IBD and TA. All were first diagnosed as IBD and the period between the diagnosis of IBD and TA was 9, 30 and 60 months, respectively. The age at diagnosis of TA was younger for the patients with IBD as compared to TA patients without IBD, but the difference was not statistically significant. Two patients had type‐5 and one had type‐2a TA. In 92 participants (52 with TA and 40 healthy controls) none had positive results for ANCA or ASCA. Conclusion: Anti‐saccharomyces antibody and ANCA tests are not useful for predicting the association between TA and IBD. On the other hand, both diseases have similar patient characteristics and pathophysiology which make us suspect that there may be an interaction. If a patient with IBD under immunosuppressive treatment has ongoing symptoms such as fever, weight loss, hypertension or high acute phase reactants, TA may be the cause. Further trials are needed but their coexistence cannot be explained as incidental.